Neuropilin-1: a checkpoint target with unique implications for cancer immunology and immunotherapy - Chang Liu; Creg J Workman; Dario AA Vignali; Christopher A Chuckran; Tullia C Bruno (Journal for ImmunoTherapy of Cancer)
Checkpoint blockade immunotherapy established a new paradigm in cancer treatment: for certain patients curative treatment requires immune reinvigoration. Despite this monumental advance, only 20%–30% of patients achieve an objective response to standard of care immunotherapy, necessitating the consideration of alternative targets. Optimal strategies will not only stimulate CD8+ T cells, but concomitantly modulate immunosuppressive cells in the tumor microenvironment (TME), most notably regulatory T cells (Treg cells). In this context, the immunoregulatory receptor Neuropilin-1 (NRP1) is garnering renewed attention as it reinforces intratumoral Treg cell function amidst inflammation in the TME. Loss of NRP1 on Treg cells in mouse models restores antitumor immunity without sacrificing peripheral tolerance. Enrichment of NRP1+ Treg cells is observed in patients across multiple malignancies with cancer, both intratumorally and in peripheral sites. Thus, targeting NRP1 may safely undermine intratumoral Treg cell fitness, permitting enhanced inflammatory responses with existing immunotherapies. Furthermore, NRP1 has been recently found to modulate tumor-specific CD8+ T cell responses. Emerging data suggest that NRP1 restricts CD8+ T cell reinvigoration in response to checkpoint inhibitors, and more importantly, acts as a barrier to the long-term durability of CD8+ T cell-mediated tumor immunosurveillance. These novel and distinct regulatory mechanisms present an exciting therapeutic opportunity. This review will discuss the growing literature on NRP1-mediated immune modulation which provides a strong rationale for categorizing NRP1 as both a key checkpoint in the TME as well as an immunotherapeutic target with promise either alone or in combination with current standard of care therapeutic regimens.